Diagnostic criteria for temporomandibular disorders—INfORM recommendations: Comprehensive and short‐form adaptations for children. (14th December 2022) - Nilsson, Ing‐Marie; Ekberg, EwaCarin; Michelotti, Ambrosina; Al‐Khotani, Amal; Alstergren, Per; Conti, Paulo Cesar Rodrigues; Durham, Justin; Goulet, Jean‐Paul; Hirsch, Christian; Kalaykova, Stanimira; Kapos, Flavia P.; King, Christopher D.; et al.
Abstract: Background: The Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) are used worldwide in adults. Until now, no adaptation for use in children has been proposed. Objective: The aim of this study was to present comprehensive and short‐form adaptations of Axis I and Axis II of the DC/TMD for adults that are appropriate for use with children in clinical and research settings. Methods: Global Delphi studies with experts in TMDs and in pain psychology identified ways of adapting the DC/TMD for children. Results: The proposed adaptation is suitable for children aged 6–9 years. Proposed changes in Axis I include (i) adapting the language of the Demographics and the Symptom Questionnaires to be developmentally appropriate for children, (ii) adding a general health questionnaire for children and one for their parents, (iii) replacing the TMD Pain Screener with the 3Q/TMD questionnaire and (iv) modifying the clinical examination protocol. Proposed changes in Axis II include (i) for the Graded Chronic Pain Scale, to be developmentally appropriate for children, (ii) adding anxiety and depression assessments that have been validated in children and (iii) adding three constructs (stress, catastrophising and sleep disorders) to assess psychosocial functioning in children. Conclusion: The recommended DC/TMD, including Axis I and Axis II, for children aged 6–9 years, is appropriate for use in clinical and research settings. This adapted the first version for children includes changes in Axis I and Axis II changes requiring reliability and validity testing in international settings. Official translations to different languages according to INfORM requirements will enable a worldwide dissemination and implementation. Abstract : These Diagnostic Criteria for Temporomandibular disorders in children were created by means of a Delphiprocess including experts in both orofacial pain and psychological domains.